Effect of pods storage and fermentation duration on bioconversion of proanthocyanidins in malaysian cocoa beans: article - Mahmun, Rabiatul ‘Adawiyah; Mohd Sauid, Suhaila; Sulaiman, Khairul Bariah (2017)
These two factors being studied where pods storage duration were varied as 0, 2, 4 and 6 days. Meanwhile, the fermentation duration of cocoa beans differs from day 0 until day 5. The sample that being ferment were defatted before undergo the extraction process. The extraction process undergo overnight by immersing the sample with the methanol solvent. The total proanthocyanidins content were analyzed by using UV Spectrophotometric and High-Performance Liquid Chromatography (HPLC) analysis. Multiple linear regression method was used in order to relate the relationship between concentrations of proanthocyanidins with the absorbance value taken from UV Spectrophotometric analysis. The regression value of this research was R² = 0.9486. The total proanthocyanidins contents in all samples from different pods storage and fermentation duration are varied from the both analyses. ANOVA analysis definitely revealed that fermentation duration has a significant effect to the bioconversion of the proanthocyanidins in Malaysian cocoa beans. Meanwhile, the pods storage might have 2.36E-08 ± 1.2E-05 effect toward bioconversion of proanthocyanidins. Since it < 0.05, it is considered negligible. It can be concluded that pods storage duration does not have significant effect to the proanthocyanidins bioconversion.